The impact of new urbanization on “quantity increase and quality improvement” of urban green innovation - Liang Fang; Chengxiang Li; Chen Jin (PLoS ONE, 2026)
With the rise of new urbanization (NEU) as a major national strategy, a proposition with both theoretical and practical significance has been highlighted. Whether the implementation of this strategy can substantially enhance the quantity and quality of urban green innovation (GI) remains a focus of ongoing attention from the government and academia. Based on panel data from 284 cities from 2011 to 2022, this study constructs two-way fixed-effects models and multivariate moderation models, and empirically analyzes the effect of NEU on the “quantity increase” and “quality improvement” of urban GI. The study finds that the coefficients for NEU’s impact on “quantity increase” and “quality improvement” of urban GI are statistically significant at the 0.01 level, with positive signs indicating enhancement effects. The moderating effect indicates that the coupling interaction between digital inclusive finance and various elements (government technology support, informatization, regional economic development, energy consumption) constitutes a gain mechanism, effectively strengthening the marginal effect of increases in the quantity and quality of urban GI. Threshold effect analysis indicates that the government’s green support exerts a threshold effect on NEU’s influence on urban GI. The paper not only deepens the understanding of the NEU dividend release mechanism but also provides operational policy implications for coordinating the two key agendas of NEU construction and GI development.